Taxonomy and ecologic biogeography of the irregular Echinoids (Echinoidea: Irregularia) from Mexico. - Martínez-Melo, Alejandra (2015)
Mexico owns 643 species of echinoderms, almost 10% of the known echinoderm species in the planet. Its geographic location -between the oceanic influences of the Western Central Atlantic and the Eastern Central Pacific- largely explains its enormous biological and ecological diversity. Research on echinoderms in Mexico began in the late nineteenth century; however, there are no reviews on its irregular echinoids. This work reviews the taxonomic and geographic information of irregular echinoids from Mexico, housed in four collections: 1) Colección Nacional de Equinodermos “Ma. Elena Caso Muñoz” from the Instituto de Ciencias del Mar y Limnología (ICML), Universidad Nacional Autónoma de México (UNAM); 2) Invertebrate Zoology Collection, Smithsonian Museum of Natural History, Washington, D.C., United States of America (USA); 3) Invertebrate Collection, Museum of Comparative Zoology, University of Harvard, Boston, Massachusetts, USA and 4) Invertebrate Zoology, Peabody Museum, Yale University, New Haven, Connecticut, USA. Specimens were reidentified and classified; geographic distribution data were subjected to a parsimony analysis of endemisms (PAE) using the ecological regionalization of North America proposed by Wilkinson et al. (2010). A total of six orders, 17 families, 35 genera and 68 species are reported, distributed in 34 ecoregions, 11 from the Atlantic coast and 23 from the Pacific coast. Nine biogeographic regions were delimited, four in the Atlantic coast and five in the Pacific coast. The biogeographic analysis suggests that the oceanic currents and sediments are the environmental factors that determine the distribution of irregular echinoids in the Mexican Atlantic coast; on the other hand, oceanic currents and depth are the environmental factors that determine the distribution of irregular echinoids in the Mexican Pacific coast.